Current approaches to sport science support in the English Premier League - Drust, B. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Sport science support within football in the UK has its foundations in the 1970`s. This initial pioneering activity, that was limited in both its scale and focus, has progressively developed across subsequent decades both within the practice of specific clubs and more generally across the league. The integration of "science" into a variety of the processes and practices of football clubs is now common across the Premier League. This can be evidenced by the existence of a number of sport science related positions within football organisations (e.g. sport scientist, fitness coach, rehabilitation strength and conditioning) and the large number of commercial products and companies aimed at supporting the performance of players (e.g. performance analysis software, physiological data collection systems, data management tools). The aims of this presentation are to provide some illustrative content related to the current application of sport science within the English Premier League. The material presented will include an example of the organisational structures used within clubs (e.g. the staffing base, communication strategies with other departments, organisational missions) and an outline of the fundamental activities frequently included to support the performance of the players. Such activities include evaluating the demands of match-play, optimally preparing players for games, planning, implementing and monitoring training programmes, injury prevention strategies and supporting performance with effective nutritional strategies. The presentation will also incorporate information on the factors that influence the application of sport science in the professional football environment. Both the limitations in the available scientific literature and the organisational/cultural framework operating within football will be discussed as these are important considerations for any applied scientific performance orientated support programme.